A longitudinal evaluation of a penetrating traumatic brain injury: Theories of plasticity and vulnerability. Issue 4 (4th July 2022) - Burns, Thomas G.; Semmel, Eric S.; Reisner, Andrew
Abstract: Penetrating traumatic brain injury (TBI) is uncommon in infancy. The consequences may be devastating, especially when the injury is extensive and affects eloquent areas of the brain. There is the potential for neuropsychological dysfunction that may impact the individual's development and well-being into adulthood. In the context of early brain injury, the developing brain is both remarkably resilient and vulnerable. The present case study describes a patient who experienced a penetrating TBI at 9 days of age, subsequently developed intractable seizures, and underwent left hemispherectomy. Neuropsychological testing at ages 5, 10, 11, and 19 years are presented alongside fMRI and Wada testing. While the patient initially developed cognitive functions in the low-average range by age 5, scores on neuropsychological assessments began to decrease thereafter. This case is discussed with attention to vulnerability and plasticity theories. It highlights the ability of the brain to reorganize and allow the development of functions that would normally be sub-served by damaged areas and the limits of plasticity. Further, this case illustrates the vulnerability of the early brain to insult, the potential to grow into deficits, and the need to consider a variety of factors when predicting outcomes for cases of pediatric brain injury.